2015
DOI: 10.1007/s00414-015-1290-3
|View full text |Cite
|
Sign up to set email alerts
|

Kinship analysis: assessment of related vs unrelated based on defined pedigrees

Abstract: The study aimed at evaluating whether the adoption of enlarged batteries of STR markers in kinship analysis may provide LR values suitable for discrimination of relatives from non-relatives, in comparison to conventionally used STR panels. The presence of LD among some loci and its effects on LR values were also assessed. Three hundred pairs of related and unrelated individuals, each separated from 1-3 generations and residing in North Italy were genotyped with the Investigator HDplex STR kit (Qiagen), AmpFlST… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 27 publications
1
3
0
Order By: Relevance
“…Studies suggest that genotyping more than 20 autosomal STR loci improve forensic personal identification, especially in the sibship analyses (Allen et al, 2007;Carboni et al, 2014;Von Wumb-Schwark et al, 2015;Tamura et al, 2015;Turrina et al, 2016), which corresponds to our findings.…”
Section: Resultssupporting
confidence: 87%
“…Studies suggest that genotyping more than 20 autosomal STR loci improve forensic personal identification, especially in the sibship analyses (Allen et al, 2007;Carboni et al, 2014;Von Wumb-Schwark et al, 2015;Tamura et al, 2015;Turrina et al, 2016), which corresponds to our findings.…”
Section: Resultssupporting
confidence: 87%
“…This finding probably is explained by the limited power of exclusion of D10S1248 and D22S1045: PE = 0.439 and 0.2709, respectively [5]. In fact, our results from real cases are complementary to those based on simulations comparing different commercial kits in complex kinship analyses, where it has been observed that the implementation of more STRs allows a strong discrimination between relatives and non-relatives (decreases false positives and false negatives) [6,7].…”
Section: Paternity Index (Pi) By Hid Kitsmentioning
confidence: 63%
“…Despite the high discriminatory power of gold-standard STR markers and the availability of the supplemental use of lineage markers, their usage could be limited in distant and complex relative testing, or only partially informative in resolving cases. 3 4 15 16 17 18 The mutation rates of STRs are known to be relatively high, which could cause difficulties in interpretation and lead to inconclusive results. It is also difficult to identify different relationships, such as differentiating between FSs and HSs.…”
Section: Discussionmentioning
confidence: 99%